The mapping and differentiation of biological and environmental elemental signatures in the fossil remains of a 50 million year old bird. Issue 3 (22nd January 2015) - Egerton, Victoria M.; Wogelius, Roy A.; Norell, Mark A.; Edwards, Nicholas P.; Sellers, William I.; Bergmann, Uwe; Sokaras, Dimosthenis; Alonso-Mori, Roberto; Ignatyev, Konstantin; van Veelen, Arjen; Anné, Jennifer; van Dongen, Bart; et al.
Abstract : Synchrotron analysis of a 50 million year old bird from the Green River Formation (USA) reveals the chemistry of preservation. Abstract : The preservation of fossils reflects the interplay of inorganic and organic chemical processes, which should be clearly differentiated to make interpretations about the biology of extinct organisms. A new coliiformes bird (mouse bird) from the ∼50 million year old Green River Formation (Wyoming, USA) has here been analysed using synchrotron X-ray fluorescence and environmental scanning electron microscopy with an attached X-ray energy dispersive system (ESEM-EDS). The concentration and distribution of 16 elements (Si, P, S, Cl, K, Ca, Ti, Mg, Fe, Ni, Cu, Zn, As, Br, Ba, Hg) has been mapped for individual points on the sample. S, Cu and Zn map distinctly within visibly preserved feathers and X-ray Absorption Spectroscopy (XAS) shows that S and Cu within the feathers are organically bound in a similar manner to modern feathers. The morphological preservation of the feathers, on both macro- and microscopic scales, is variable throughout the fossil and the differences in the lateral microfacies have resulted in a morphological preservation gradient. This study clearly differentiates endogenous organic remains from those representing exogenous overprinted geochemical precipitates and illustrates the chemical complexity of the overall taphonomic process.